TINGKAT KESUKAAN KONSUMEN TERHADAP PRODUK KUE NASTAR DENGAN ISIAN SELAI KACANG HIJAU KEJU DAN SELAI KACANG HIJAU COKELAT DITINJAU DARI UJI ORGANOLEPTIK - Yuliana Daiman; Yunus Karyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Nastar cookies are among the most popular traditional cookies in Indonesia, commonly filled with pineapple jam. Mung beans can be utilized as an alternative filling due to their high nutritional value and favorable sensory characteristics, and the combination of mung bean jam with cheese and chocolate is expected to provide appealing flavor variations. This study aimed to determine the level of consumer preference toward nastar cookies filled with mung bean jam and cheese and mung bean jam and chocolate based on organoleptic evaluation, including color, aroma, taste, and texture. This study employed an experimental method with a quantitative approach and a posttest-only design involving 50 untrained panelists in the Ngagel Dadi area of Surabaya, selected through purposive sampling and the Slovin formula. Data were collected through organoleptic testing using a 5-point hedonic scale questionnaire on two treatments, namely nastar filled with mung bean jam and cheese (Sample A) and nastar filled with mung bean jam and chocolate (Sample B), then analyzed descriptively and examined using a Paired Sample t-Test at a significance level of 0.05. The results showed that both variants were categorized as liked to highly liked, with Sample A obtaining higher mean scores than Sample B across all attributes. The Paired Sample t-Test showed a significance value of 0.000 (<0.05) for all attributes, indicating a significant difference in preference between the two variants, with taste showing the largest mean difference. Thus, the innovation of nastar cookies based on mung bean jam demonstrated good consumer acceptance and has potential to be developed as a local ingredient-based food product.